2016
DOI: 10.4084/mjhid.2016.003
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Response Associated With Hepatitis C Virus Clearance in Hiv Coinfected Patients Initiating Peg Interferon- Based Therapy.

Abstract: BackgroundTreatment of hepatitis C virus (HCV) infection based on peginterferon-α (pegIFNα) and ribavirin induces important changes in cytokine release and T cell activation.ObjectiveImmune response to pegIFNα-ribavirin therapy was explored in patients coinfected by HCV and HIV.MethodsConcentrations of 25 cytokines and CD8+ T cell activation were monitored in HCV/HIV coinfected patients classified as sustained virological responders (SVR, n=19) and non-responders (NR, n=11).ResultsHigh pretreatment concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…1 ), suggesting the synergistic effects of poly (I: C) and imiquimod on MoDCs presenting PRRSV antigen. By the way, Th2-type cytokine IL-4 expressed in MoDCs was very low and hard to be detected, so IL-6 and IL-10 were chosen to detect in our study as reported 35 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ), suggesting the synergistic effects of poly (I: C) and imiquimod on MoDCs presenting PRRSV antigen. By the way, Th2-type cytokine IL-4 expressed in MoDCs was very low and hard to be detected, so IL-6 and IL-10 were chosen to detect in our study as reported 35 36 .…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a transcription factor that regulates the expression of a large number of genes including those involved in inflammation. NF-κB also plays an essential role in innate immune response and many signaling pathways are associated with NF-κB 33 36 37 38 . In previous studies, TRIF mediated innate immune responses in peritoneal mesothelial cells through TLR3 and TLR4 stimulation via activation of NF-κB or MAPKs 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the mechanisms underlying IR during the different treatment regimens for HCV is of great importance because the SVR is influenced by the host IR, as previously established by studies on patients undergoing dual therapy 14,17,21,26 . In particular, previous findings indicated that the production of cytokines and chemokines plays an important role in the IR during HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, including the IR, are associated with low SVR rates 10 . Several studies have attempted to further investigate the mechanisms underlying the above findings [11][12][13][14][15] ; however, the results remained ambiguous and controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation